The table olive sector [printed version also available in Arabic] - Murchid Rachid M.; Soulaiman A.H.; Rayab G.; Lovino R. (Syrian national strategic plan for olive oil quality : final report, 2007)
The sub-project Processing of table olive, supported by Italian and Syrian Government institutions, intended to promote table olive production in Syria. The main tasks have been the updating of state-of-art of raw and processed material production; a survey of main applied technologies and factories; the training of experts in processing and quality control of the table olive; the building of a new laboratory for the production of table olive. The state-of-art of raw and processed material production has been defined through a survey of the technologies used by the main Syrian Companies.